Materials characterization for Refuse Derived Fuel (RDF) production as renewable energy resources - I Made Wahyu Wijaya; I Gusti Ngurah Made Wiratama; I Kadek Ardi Putra (Center for Science and Technology, IAIN Surakarta, 2024)
This study offers a comprehensive analysis of key parameters—volatile matter, carbon content, ash content, and gross energy—across various material samples intended for Refused Derived Fuel (RDF) briquette production. Through meticulous examination, promising trends emerge, highlighting optimal material combinations for efficient combustion and heat generation. Samples rich in volatile matter and carbon content, notably those incorporating wood powder, demonstrate elevated calorific values, indicating their potential for effective energy production. Conversely, material combinations with low ash content suggest cleaner combustion and reduced environmental impact. The gross energy analysis further validates the substantial heat generation potential of specific sample combinations, rendering them suitable for diverse heating applications. These findings emphasize the critical role of precise raw material selection and meticulous manufacturing process optimization in producing RDF briquettes with desirable properties. Such briquettes not only offer economic viability but also contribute to environmental sustainability by providing an alternative fuel source with reduced emissions. This research underscores the importance of continued exploration and refinement in the development of RDF briquettes, aiming to meet growing energy demands while mitigating environmental concerns.